Runoff simulation and analysis of water source in the high-altitude and cold region of the Shaliu River Basin - Yunying Wang; Zongxing Li; Zongjie Li; Baijuan Zhang; Guohui Li; Lanping Si (Journal of Hydrology: Regional Studies)
Study Region: The Shaliu river basin, a small basin in a high-altitude cold region. Study Focus: An improved SWAT model was used to simulate monthly runoff from 1960 to 2022. The snowmelt module was improved using a dual-factor method of temperature and radiation, and the surface runoff module was optimized under the condition of permafrost presence. The period from 1960 to 1964 was used as the model warm-up period, 1965–2000 as the calibration period, and 2001–2022 as the validation period. The study quantified the contributions of different components of the basin to runoff, analyzed the changes in blue and green water, and assessed the contributions of meteorological factors to runoff changes. New Hydrological Insights for the Region: The study identified CN2, GW_DELAY, SOL_BD, and ESCO as the key parameters affecting annual runoff changes. The improved SWAT model showed better performance in simulating runoff, especially during snowmelt and permafrost periods, with improved R² 0.686 to 0.702), reduced PBIAS (by 4.8 %), and increased NSE (by 0.041) in the calibration period. The snowmelt contribution rate was 6.5 %, peaking in spring, The contribution of snowmelt is decreasing with time and the contribution of baseflow is increasing on time scales. Blue water increased significantly annually, green water decreased slightly, and the green water coefficient decreased. The highest values were observed in August. Spatially, green water was higher in the middle and lower at both ends, blue water was higher upstream, and the green water coefficient was lower upstream. At the basin scale, green water was more abundant than blue water. Precipitation, temperature, and relative humidity were the main factors affecting runoff changes. This study offers a theoretical basis for water resource management in cold-region watersheds.